Fungal pathogens of canker disease trigger canopy dieback in poplar saplings by inducing functional failure of the phloem and cambium and carbon starvation in the xylem. (December 2020) - Xing, Junchao; Li, Ping; Zhang, Yinan; Li, Jinxin; Liu, Ya; Lachenbruch, Barbara; Su, Xiaohua; Zhao, Jiaping
Abstract: Tree canker diseases are mainly caused by necrotrophic fungal pathogens, which induce canker lesions, wilting, or dieback in many species. We hypothesized that canker-associated canopy dieback is related to functional failure of the phloem and cambium, carbon starvation and/or hydraulic failure. Using a girdling and inoculation system, we evaluated gas exchange and hydraulic parameters, concentrations of non-structural carbohydrates (NSCs), leaf characteristics, stem phenotyping and symptoms of 6-month-old poplar saplings with Botryosphaeria or Valsa canker disease. Pathogen inoculations inhibited callus formation and phloem regeneration and altered the physiological parameters, water potential, NSC content in stems, and symptoms on leaves and stems, while the girdling-only control did not. Results suggest that the functional and structural integrity of the phloem and cambium play crucial roles in the pathogenesis of canker disease. Botryosphaeria canker decreased photosynthetic rate (−54% to −75%), stomatal conductance (−71% to −80%) and transpiration rate (−58% to −66%), while Valsa canker decreased photosynthetic rate (−53% to −83%), stomatal conductance (−71% to −87%) and transpiration rate (−53% to −76%) at 20, 25, and 30 days after inoculation. Results suggest that the two fungal pathogens induce carbon starvation by inhibiting photosynthesis. The leaf water potential was higher and the change in specific hydraulic conductivity was smaller in the canker region than in the adjacent regions, while the NSC content was lower in the region below cankers than above them, suggesting that the fungal pathogens caused poplar canopy dieback by initially inducing carbon starvation, not hydraulic failure. Highlights: A novel girdling-inoculation method was used to reveal the physiology of poplar Botryosphaeria dothidea and Valsa sordida diseases . The functional integrity of phloem and cambium plays crucial roles in the development of cankers. Pathogens B. dothidea and V. sordida induce carbon starvation by inhibiting photosynthesis. The development of cankers initially due to carbon starvation, not hydraulic failure, in the early stage of diseases. Pathogens change the path of water movement, suggesting an inhibition of water conductivity in the late stage of poplar canker diseases.